Management of abdominal pseudotumours in haemophilia: a systematic review (Swiss Medical Weekly, 2023)
AIM: Haemophilic pseudotumours are complications in patients with haemophilia A or B and result from locally repetitive bleeding, mainly in the musculoskeletal system. Abdominal haemophilic pseudotumours are exceptionally rare but may cause severe complications. This systematic review aimed to evaluate therapy strategies for symptomatic abdominal haemophilic pseudotumours.METHODS: We systematically searched three databases (Medline [PubMed], Web of Science and EMBASE) for publications published between 1995 and 2023. Two reviewers independently selected the studies, extracted data and performed a quality assessment using the JBI critical appraisal checklist.RESULTS: From a total of 1199 articles, 39 articles describing 41 cases were included for final analysis. Conservative or interventional treatment was performed in 12 cases. In eight cases, a step-up to surgical therapy after interventional treatment was indicated. Primary surgical therapy was performed in 21 cases. Failure to cure was documented in 50% (n = 6) of patients treated in the first group, with a mortality rate of 16.6% (n = 2). Interventional therapy with a step-up to surgery showed no morbidity or mortality. Primary surgical resection documented favourable results in 66.6% (n = 14), with failure to cure in 9.5% (n = 2) and a mortality rate of 14.3% (n = 3).CONCLUSION: Primary surgical resection can be a first-line therapy for symptomatic, abdominal haemophilic pseudotumours, whereas preoperative embolisation could be used as a bridging therapy before surgery, especially in emergency settings. Diagnostic biopsy and percutaneous drainage should be avoided to prevent complications.